The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1017/s1368980015001548
|View full text |Cite
|
Sign up to set email alerts
|

Speed of eating and 3-year BMI change: a nationwide prospective study of mid-age women

Abstract: Objective: To conduct the first nationwide population survey to examine the associations between changes in speed of eating and weight gain over 3 years. The study also explored whether faster eating at baseline was related to healthyweight women becoming overweight after 3 years. Design: Longitudinal. At baseline, participants were randomly selected from a nationally representative sampling frame to participate in a prospective study. Women completed self-administered baseline questionnaires on demographic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 26 publications
0
18
1
Order By: Relevance
“…with responses including: "very slow", "relatively slow", "medium", "relatively fast", or "very fast". Results from this study demonstrated that, unlike the results from other cross-sectional studies, there were no associations with eating speed and BMI: neither faster eating at baseline nor change in speed of eating over the 3 year period increased the risk of becoming overweight (24). Because the relationship between eating rate and body weight remains undefined, additional studies are warranted.…”
Section: Eating Ratecontrasting
confidence: 85%
See 2 more Smart Citations
“…with responses including: "very slow", "relatively slow", "medium", "relatively fast", or "very fast". Results from this study demonstrated that, unlike the results from other cross-sectional studies, there were no associations with eating speed and BMI: neither faster eating at baseline nor change in speed of eating over the 3 year period increased the risk of becoming overweight (24). Because the relationship between eating rate and body weight remains undefined, additional studies are warranted.…”
Section: Eating Ratecontrasting
confidence: 85%
“…It has been postulated that increased ingestion rate is positively associated with body weight (22,23); however, one prospective trial showed that faster eating or a change in eating speed was not associated with increased risk for obesity at 3 years (24). Therefore, this association is still undefined.…”
Section: Slow Eating Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, after adjusting for possible confounders, this association only remained in women [10]. Only two longitudinal studies in healthy populations—one from New Zealand [11] conducted in women, and the other from Japan [12] conducted in men—have analyzed the association between eating speed and weight change, and positive associations were reported in both. A recent longitudinal study conducted in a Japanese population with type 2 diabetes mellitus (T2DM) showed that those individuals eating slower at baseline had a lower prevalence of obesity [13] and had lower BMIs and waist circumferences than those eating fast after 6 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a systematic review and meta-analysis of several cross-sectional [7,8,9,10] and longitudinal [11,12,13] studies, most of which were conducted in Asian populations, showed that eating quickly is associated with increased body mass index (BMI) and a greater risk of obesity [14]. However, the magnitudes of association across studies were significantly heterogeneous, something that was attributed to differences between the populations studied and to the methods used to measure eating speed (self-reported eating speed or self-reported eating rate) [14].…”
Section: Introductionmentioning
confidence: 99%